Increasing Students’ Awareness and Motivation to Learn English for Tourism at English Department of UNMA Banten by Involving Local Wisdom in Citorek Lebak Banten - Hamer, Welliam; Rohimajaya, Nur Azmi; Novari, Ari Fajria; Gumelar, Rizdki Elang; Riandi, Riandi; Munawaroh, Tatu; Jubaedah, Dedeh (Jurnal Pengabdian Pada Masyarakat, 2025)
Tourism plays a significant role in regional economic growth, especially in areas with unique cultural and natural attractions. As global tourism continues to expand, the ability to communicate in English has become essential for individuals involved in the tourism sector. This article aims at increasing students' awareness and motivation to learn English for Tourism through local wisdom in Citorek village, Lebak regency, Banten. Specifically, students are expected to have (1) communication skills; students need the ability to communicate with foreign tourists, from providing information to serving their needs, (2) knowledge about the destination; students must understand the ins and outs of tourist destinations in Citorek Lebak, including history, culture and tourist attractions, (3) offering skills; students need to master the skills of offering tourism products and services in English, such as accommodation, culinary delights and tourist activities, as well as (4) career preparation; mastering English opens up career opportunities for students in the tourism industry. Local wisdom is a valuable asset that can be integrated into learning english for tourism. With the right strategy, students can improve their English skills and contribute to tourism development in Citorek Lebak Banten.